Genetic polymorphism analysis of 5' untranslated region of thyroglobulin gene in Bali cattle (Bos javanicus) from three different regions of Indonesia - Anwar, S.; Putra, A.C.; Wulandari, A.S.; Agung, P. P.; Putra, W.P.B.; Said, S. (Journal of the Indonesian Tropical Animal Agriculture, 2017)
The g.422C>T nucleotide variations in the 5’ untranslated region (5’UTR) of TG gene (called as TG5) has been reported to be associated with level in intramuscular fat (IMF) content or marbling in beef cattle. The objective of this study was to confirm genetic polymorphism of TG5 gene in Bali cattle populations from three different regions as the main resources of Bali cattle in Indonesia. A total of 200 head of Bali cattle have been performed genotyping on TG5 gene using polymerase chain reaction-restriction fragment lenght polymorphism (PCR-RFLP) method and sequence analysis. Results of the study confirmed that TG5 was monomorphic in Bali cattle wherever their origin regions. Moreover, nine candidate SNPs were detected within 5’UTR of TG gene in Bali cattle compared to Genbank reference sequences, although no SNP variations among Bali cattle sample studied. The new other genetic markers within an entire TG gene suggested to be explored and verified for their polymorphisms in Bali cattle. The nine candidate SNPs were also required further verification and validation in a larger sample to be regarded as new SNPs between Bali cattle and Genbank reference sequences.